Towards model checking product lines in the digital humanities: an application to historical data - Breathnach, Ciara; Muhamad Ibrahim, Najhan; Clancy, Stuart; Margaria, Tiziana (Springer, 2019)
Rapid development in computing techniques and databases’ systems have aided in the digitization of, and access to, various historical (big) data, with significant challenges of analysis and interoperability. The Death and Burial Data, Ireland project aims to build a Big Data interoperability framework loosely based on the Knowledge Discovery Data (KDD) process to integrate Civil Registration of Death data with other data types collated in Ireland from 1864 to 1922.